S133 The assessment of health related quality of life in interstitial lung disease with the King's brief interstitial lung disease questionnaire (K-BILD). (2nd December 2011) - Patel, A S; Siegert, R; Brignall, K; Keir, G; Bajwah, S; Desai, S R; Wells, A U; Higginson, I J; Birring, S S
Abstract : Introduction: The King's brief interstitial lung disease questionnaire (K-BILD) is a recently developed and validated 15 item HRQOL questionnaire comprising of 3 health domains (psychological, breathlessness and activities, and chest symptoms) and an overall HRQOL score. We set out to evaluate HRQOL in a large group of patients with interstitial lung diseases (ILD's) and determine the factors that influence it. Methods: 219 patients with ILD (60 idiopathic pulmonary fibrosis (IPF), 81 connective tissue associated ILD, 23 idiopathic non-specific interstitial pneumonitis (NSIP), 21 hypersensitivity pneumonitis, 10 organising pneumonia, 24 other) attending ILD clinics at King's College and Royal Brompton Hospitals completed the K-BILD. The K-BILD Scores range from 0 to 100, with a higher score representing a better HRQOL. Demographic data, immunosuppressant medication, long-term oxygen therapy use, multi-disciplinary team ILD diagnosis and lung function were recorded. Results: Patients had a mean (SEM) age of 60 (1) years, 75% of patients were Caucasian, 60% were females, mean (SEM) VC% predicted was 80 (24) % and TLCO % predicted was 47 (18)%. HRQOL was impaired in all domains, mean (SEM) scores: psychological 62 (2), breathlessness and activities 43 (2), chest symptoms 67 (2), total 59 (2). There were no significant associations between overall HRQOL and age (r=−0.007) or gender (p=0.13). There was a modest correlation between HRQOL and lung function (Abstract S133 table 1 ). HRQOL was significantly lower in IPF patients compared to other ILD's (total score 51 (3) vs 62 (2); p<0.01), those with UIP pattern vs NSIP (total score 51 (3) vs 62 (3); p<0.01) and those prescribed long-term oxygen therapy (total score 38 (4) vs 63 (2); p<0.01). IPF patients prescribed immunosuppressant medication had significantly worse overall HRQOL (48 (4) vs 74 (8); p=0.02). There was no significant difference between CTD-NSIP patients compared with idiopathic NSIP (total score 62 (3) vs 62 (5); p=0.91). Conclusions: HRQOL is impaired in patients with ILD. The type of ILD, immunosuppressant medication, and lung function all influence HRQOL. This study provides further clinical validation of the K-BILD.